Chemical enrichment in isolated barred spiral galaxies. Issue 4 (14th April 2018) - Martel, Hugo; Carles, Christian; Robichaud, Fidèle; Ellison, Sara L; Williamson, David J
Abstract: To investigate the role of bars in the chemical evolution of isolated disc galaxies, we performed a series of 39 gas dynamical simulations of isolated barred and unbarred galaxies with various masses, initial gas fractions, and active galactic nucleus (AGN) feedback models. The presence of a bar drives a substantial amount of gas towards the central region of the galaxy. In the most massive galaxies, this results in a violent starburst, followed by a drop in star formation resulting from gas exhaustion. The time delay between Type Ia and Type II supernovae explosions means that barred galaxies experience a rapid increase in [O/H] in the central region, and a much more gradual increase in [Fe/H] . In unbarred galaxies, star formation proceeds at a slow and steady rate, and oxygen and iron are produced at steady rates which are similar except for a time offset. Comparing the abundance ratios in barred and unbarred galaxies with the same central stellar mass M *, we find in barred galaxies an enhancement of 0.07 dex in [O/H], 0.05 dex in [Fe/H], and 0.05 dex in [O/Fe] . The [O/H] enhancement is in excellent agreement with observations from the SDSS . The initial gas fraction has very little effect on the abundance ratios in barred and unbarred galaxies, unless the galaxies experience a starburst. We considered AGN-host galaxies located near the bottom of the AGN regime, M * ≳ 3 × 10 10 M ⊙, where AGN feedback dominates over supernovae feedback. We found that the impact of AGN feedback on the central abundances is marginal.